Stimulation of lymphangiogenesis via VEGFR-3 inhibits chronic skin inflammation - Huggenberger, Reto (The Rockefeller University Press, 2010)
The role of lymphangiogenesis in inflammation has remained unclear. To investigate the role of lymphatic versus blood vasculature in chronic skin inflammation, we inhibited vascular endothelial growth factor (VEGF) receptor (VEGFR) signaling by function-blocking antibodies in the established keratin 14 (K14)–VEGF-A transgenic (Tg) mouse model of chronic cutaneous inflammation. Although treatment with an anti–VEGFR-2 antibody inhibited skin inflammation, epidermal hyperplasia, inflammatory infiltration, and angiogenesis, systemic inhibition of VEGFR-3, surprisingly, increased inflammatory edema formation and inflammatory cell accumulation despite inhibition of lymphangiogenesis. Importantly, chronic Tg delivery of the lymphangiogenic factor VEGF-C to the skin of K14-VEGF-A mice completely inhibited development of chronic skin inflammation, epidermal hyperplasia and abnormal differentiation, and accumulation of CD8 T cells. Similar results were found after Tg delivery of mouse VEGF-D that only activates VEGFR-3 but not VEGFR-2. Moreover, intracutaneous injection of recombinant VEGF-C156S, which only activates VEGFR-3, significantly reduced inflammation. Although lymphatic drainage was inhibited in chronic skin inflammation, it was enhanced by Tg VEGF-C delivery. Together, these results reveal an unanticipated active role of lymphatic vessels in controlling chronic inflammation. Stimulation of functional lymphangiogenesis via VEGFR-3, in addition to antiangiogenic therapy, might therefore serve as a novel strategy to treat chronic inflammatory disorders of the skin and possibly also other organs.